ERROR ANALYSIS ON STORY TELLING BY PARTICIPANTS OF STORY TELLING COMPETITION IN “SMART EDUCATION CENTER COURSE” - SILITONGA, SUGENG (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Error, Error Analysis, Surface Strategy Taxonomy, Story TellingUnderstanding the grammatical structure of target language is one of the ways to determine how far a learner understands the target language.The learner can show his understanding of the target language from some ways. One of them is by having competition. In this study, the writer analyzed the error which occured in story telling done by Smart Education Center (SEC) courseparticipants. Furthermore, the writer proposed three problems of the study,(1)What errors found in the story telling of the palrtcipants (2).What errors mostfrequently made by the participants? (3).What the causes of the errors were?In the process of learning the second language, the learner sometimesproduces some errors and Error Analysis (EA) has a methodology to figure themout. One of the methodologies used is surface strategy taxonomy by Dulay (Dulay et al, 1982, p.150). In dealing with the sources of errors, the writer used the theory of Richard (as cited by Ellis,1994, p.58) which divides them into three categories namely, developmental, interference, and intralingual.This study revealed that there were 151 errors which were divided into91 misformations, 5 misorderings, 19 additions, and 36 ommisions. In terms ofsource of error, the writer found 50 (33%) intralingual error and 101 (67%)interference error. All errors were categorized as developmental error occuringfrom limited language experience. In terms of general type of error, the writercategorized all errors into local error because the errors which occured did notblock the meaning of sentences or phrases.The writer suggests to the next researcher who wants to conduct thesimilar research to use another subject and theory. Furthermore, the writersuggests him to find another criteria in determining the subject. In this research,the writer used the class and times of practicing, the next researcher can use thescore of speaking as the criteria.